Plasmolysis: Loss of Turgor and Beyond - Lang, Ingeborg; Sassmann, Stefan; Schmidt, Brigitte; Komis, George (Plants (Basel, Switzerland), 2014)
Plasmolysis is a typical response of plant cells exposed to hyperosmotic stress. The loss of turgor causes the violent detachment of the living protoplast from the cell wall. The plasmolytic process is mainly driven by the vacuole. Plasmolysis is reversible (deplasmolysis) and characteristic to living plant cells. Obviously, dramatic structural changes are required to fulfill a plasmolytic cycle. In the present paper, the fate of cortical microtubules and actin microfilaments is documented throughout a plasmolytic cycle in living cells of green fluorescent protein (GFP) tagged Arabidopsis lines. While the microtubules became wavy and highly bundled during plasmolysis, cortical filamentous actin remained in close vicinity to the plasma membrane lining the sites of concave plasmolysis and adjusting readily to the diminished size of the protoplast. During deplasmolysis, cortical microtubule re-organization progressed slowly and required up to 24 h to complete the restoration of the original pre-plasmolytic pattern. Actin microfilaments, again, recovered faster and organelle movement remained intact throughout the whole process. In summary, the hydrostatic skeleton resulting from the osmotic state of the plant vacuole "overrules" the stabilization by cortical cytoskeletal elements.
Keywords: plasmolysis; GFP-TUA6; actin microfilaments; deplasmolysis; GFP-MAP4; cytoskeleton; microtubules; Arabidopsis hypocotyl; GFP-ABD